Correlation between Body Composition and Peak Expiratory Flow Rate in First-Year Medical Students of Diponegoro University - Timothy Jordan; Darmawati Ayu Indraswari; Edwin Basyar; Buwono Puruhito (Jurnal Respirologi Indonesia, 2023)
Background: Peak expiratory flow rate (PEFR) is one of the pulmonary ventilation parameters that affects quality of life. PEFR is known to be negatively affected by high body mass index (BMI) and waist circumference (WC). This study aimed to determine the correlation of BMI and WC with PEFR in first-year medical undergraduates at Diponegoro University.Methods: This was a cross-sectional study held from October 5th to October 8th, 2020, which measured the BMI, WC, and PEFR of 169 first-year medical students at Diponegoro University. The BMI, WC, and PEFR were assessed using a digital scale, measuring tape, and Mini-Wright peak flow meter (PFM), respectively. Spearman test was used for bivariate analysis, whereas the multiple regression method was used for multivariate analysis. The results are considered significant if P <0,05 for bivariate and F <0,05 for multivariate analysis. The IBM SPSS Statistics 26.0 Software was used for statistical analysis.Results: Most of the subjects had normal BMI, with a mean value of 23.38 (±0.36) kg/m2. As many as 71.6% of the subjects had normal WC. There was a correlation between BMI and PEFR (P = 0.001) with a weak strength (R = 0.260). As for BMI, WC also demonstrated a significant positive correlation (P <0.001) with a weak strength (R = 0.342) towards PEFR. Simultaneously, both BMI and WC had a significant positive correlation (F <0.001) with a weak strength (R = 0.361) towards PEFR.Conclusion: Higher BMI and WC values coincided with higher PEFR values.